Engaging Blind Student in English Translation Class: A Report on Differentiated Instruction Implementation - Braja Perkasa Bimantoro; Alies Poetri Lintangsari; Destina Wulandari (Fakultas Ilmu Budaya, Universitas Brawijaya, 2021)
English Language Teaching practices in Indonesia have challenged the diversity including cultural background, values, customs, beliefs as well as the disability. As Indonesia ratified CRPD (Convention on the Rights of People with Disabilities) and passed the Education ministry number 46 of 2017 about special support for students with special needs, the inclusion of students with disability in higher education is increasing. Implementing differentiated instruction for Inclusive education in English language teaching practices is one of the strategies to fulfill and accommodate students with special needs. This research aims at reporting the implementation of differentiated instruction to increase the engagement of students with visual disabilities in learning English in mainstream class. The participant is a totally blind student who attended English translation class. Employing the qualitative research design, this research documented the differentiated instruction implementation by observation and interview. Implication and recommendation are postulated as resourceful insight to encourage inclusive ELT practices. English Language Teaching practices in Indonesia have challenged the diversity including cultural background, values, customs, beliefs as well as the disability. As Indonesia ratified CRPD (Convention on the Rights of People with Disabilities) and passed the Education ministry number 46 of 2017 about special support for students with special needs, the inclusion of students with disability in higher education is increasing. Implementing differentiated instruction for Inclusive education in English language teaching practices is one of the strategies to fulfill and accommodate students with special needs. This research aims at reporting the implementation of differentiated instruction to increase the engagement of students with visual disabilities in learning English in mainstream class. The participant is a totally blind student who attended English translation class. Employing the qualitative research design, this research documented the differentiated instruction implementation by observation and interview. Implication and recommendation are postulated as resourceful insight to encourage inclusive ELT practices.